An ADARPEF survey on respiratory management in pediatric anesthesia. Issue 10 (20th August 2014) - Fesseau, Roselyne; Alacoque, Xavier; Larcher, Claire; Morel, Lydia; Lepage, Benoît; Kern, Delphine; Anderson, Brian
Summary Background There have been recent changes with regard to tools and concepts for respiratory management of children undergoing general anesthesia. Objectives To determine the practice of pediatric anesthetists concerning: preoxygenation, breathing systems, ventilation modes, anesthetic agent and airway device, strategies for a general anaesthetic of less than 30 min using spontaneous respiration, and opinion about technical aspects of ventilation. Methods Online questionnaire sent by e‐mail to all the anesthetists registered on the mailing list of the French‐speaking Pediatric Anesthetists and Intensivists Association (ADARPEF). Results 232 questionnaires (46%) were returned. More than 25% of anesthetists surveyed declared that they do not perform preoxygenation before induction for children <15 years old, apart from neonates and clinical specific situations. When performed, <65% chose a FiO2 higher than 80%. Inhalational induction with sevoflurane is the preferred mode of induction set at 6% or 8%, respectively, 69% [62–75] vs 25% [18–31]. For induction, the circle system was the most popular circuit used in all ages. The accessory breathing system—Mapleson B type—was predominantly used for neonates (44% [37–54]). For maintenance of an anesthesia lasting <30 min in spontaneous breathing, the use of laryngeal mask increased with age, and the endotracheal tube was reserved for neonates (40% [33–48]). Pressure support ventilation was rarely used from the beginning of induction but was widely used for maintenance, whatever the age‐group. Results differed according to the type of institution. Conclusion Ventilation management depends on the age and institutions in terms of circuit, airway device or ventilation mode, and specific differences exist for neonates.